NOVEL SELF-NANOEMULSION DRUG DELIVERY SYSTEM OF FENOFIBRATE WITH IMPROVED BIO-AVAILABILITY. - S. VANITASAGAR; N.J.P.SUBHASHINI (International Journal of Pharma and Bio Sciences, 2013)
Fenofibrate is a very potent and highly effective lipid lowering agent, used in the treatment of hypercholesteremia with poor water solubility and dissolution rate. The objective of the study was to develop SNEDDS of fenofibrate with improved dissolution rate and to characterize for particle size, self-nanoemulsification, and dissolution enhancement. Solubility of fenofibrate was determined in various oils, surfactants, and cosurfactants. meglyoil was selected as oil phase, Cremophore RH-40 as surfactant, and PEG-400 as cosurfactant due to their higher solubilization effect. The Results of the present research indicates that the in-vitro dissolution and intestinal permeability of the developed formulation was increased when compared with that of pure drug. The mean globule size (n=3) was observed to be (< 100nm), and the zeta potential was negative which may not interfere in the absorption of the formulation. Therefore the optimised formulation exhibits improved dissolution rate when compares with pure drug.